Keanekaragaman Makrozoobentos di Aliran Sungai Rombok Banangar Kabupaten Landak Kalimantan Barat - Riza Linda, Frediktus Jhonatan, Tri Rima Setyawati, (Universitas Tanjungpura, 2016)
Benthos are organisms that live on bottom of the water body, either in the form of animals and plants, living on the surface or in the bottom of the water. This research animed to find out the diversity of the species of macrozoobenthos in the Rombok Banangar River. The research began from November 2013 until January 2014. The samples of macrozoobenthos were collected using the Surber net and Ekman Grab based on the differences of the substrate on the riverbed. The macrozoobenthos found in the Rombok Banangar River were comprised of two Phyla i.e. Arthropods and Mollusks. The Phyla of Arthropods found were of the Insect class which falls into the genera Hydropsyche, Polycentropus, psephenus, Dryops, Anthopotamu, Acroneuria and Triops. Phyla of Mollusks found were of the Bilvavia class which falls into the Genus of Corbicula and of the Gastropod class of the Genera of Melanoides and Melanatria. The highest abudanceof the macrozoobenthos at each station was Polycentropus (66,67 ind/L) and Potadoma (266,67 ind/L). The highest abudance of the macrozoobenthos found was the Melanatria at 622,2 ind/L. Based on the values of Diversity index (H) (0,367 – 0,602) dominace index (C) (0,132 – 0,386) and evenness index (E) (0,367 – 0,602) the Rombok Banangar River falls into the category of good condition with a high species diversity. The physical and chemical factors of the water body are able to support the life of the macrozoobenthos.